Finite element analysis and in vitro simulation experiments on ophthalmic trocar needles - Sun, Jiexin; Zhang, Zezhong; Yuan, Hailun; Zhao, Gaiping (Frontiers in Bioengineering and Biotechnology, 2026)
IntroductionOphthalmic trocar systems are commonly used to establish a passage into the vitreous cavity in complex ophthalmic surgeries, and optimizing the design of trocar needles may potentially reduce surgical trauma and the risk of complications.MethodsStudy combined in vitro simulation tests with finite element analysis, in details, four trocar needles with varying outer diameters (23G and 25G), bevel lengths and tip quadrilateral surface areas were evaluated. In vitro penetration force tests and penetration force measurement were performed to explore the impact of each trocar needles’ parameters on its performance, while finite element analysis was introduced to reveal phasic characteristics of stress distribution in scleral tissue during needle penetration and correlation between stress distribution and the needle tip structure.ResultsIn penetration force tests, the penetration force of the 25G needles was 14.62% lower than that of the 23G group (P < 0.001), cause a smaller needle diameter increased penetration efficiency. Further findings showed that the 23G needles with a smaller needle tip surface and longer bevel had a significantly lower penetration force than the 25G needle (P < 0.01), which indicated that bevel length along with the tip surface play vital roles in penetration efficiency. The penetration force measurement results showed that an optimal range of tip quadrilateral surface areas led to better tip strength performance. Finite element analysis found that the initial stress concentration was primarily determined by the geometry of the needle tip, while the diameter and surface properties of the needle shaft influence the stress distribution throughout the penetrating process, which interpreted the data in vitro. The smaller tip area led to more concentrated stress, and a longer bevel can distribute stress, reduce resistance during the penetration process and improve penetration efficiency.DiscussionThis study proved that a multi-stage tapering needle with apex truncated and a reasonable bevel length enhanced the strength of the needle tip while improving cutting efficiency, and provided scientific basis for designing ophthalmic trocar systems. Clinical studies could be taken in the further to meet the ophthalmic surgery developing toward greater precision and minimal invasiveness.